Ganong's review of medical physiology - 4 0 16; Barrett, Kim E;Ganong, William F.; 5 (New York :;London : McGraw-Hill Medical ;;McGraw-Hill [distributor], 2012)
The field's most complete, up-to-date, and engagingly written text on medical physiology -- presented in full color -- 600 full-color illustrations. Concisely covering every important topic without sacrificing depth or readability, Ganong's delivers more detailed, clinically-relevant, high-yield information per page than any similar text or review. Thoroughly updated to reflect the latest research and developments in important areas such as the cellular basis of neurophysiology, this book incorporates examples from clinical medicine throughout the chapters to illustrate important physiologic concepts. Whether you're a student who needs an outstanding review for the USMLE or a physician who wants to keep pace with the ever-changing field of medical physiology
General principles & energy production in medical physiology -- Overview of cellular physiology in medical physiology -- Immunity, infection, & inflammation -- Excitable tissue: nerve -- Excitable tissue: muscle -- Synaptic & junctional transmission -- Neurotransmitters & neuromodulators -- Somatosensory neurotransmission: touch, pain, and temperature -- Vision -- Hearing & equilibrium -- Smell & taste -- Reflex and voluntary control of posture & movement -- Autonomic nervous system -- Electrical activity of the brain, sleep-wake states, & circadian rhythms -- Learning, memory, language & speech -- Basic concepts of endocrine regulation -- Hypothalamic regulation of hormonal functions -- The pituitary gland -- The thyroid gland -- The adrenal medulla & adrenal cortex -- Hormonal control of calcium & phosphate metabolism & the physiology of bone -- Reproductive development & function of the female reproductive system -- Function of the male reproductive system -- Endocrine functions of the pancreas & regulation of carbohydrate metabolism -- Overview of gastrointestinal function & regulation -- Digestion, absorption, & nutritional principles -- Gastrointestinal motility -- Transport & metabolic functions of the liver -- Origin of the heartbeat & the electrical activity of the heart -- The heart as a pump -- Blood as a circulatory fluid & the dynamics of blood & lymph flow -- Cardiovascular regulatory mechanisms -- Circulation through special regions -- Introduction to pulmonary structure and mechanics -- Gas transport & pH -- Regulation of respiration -- Renal function & micturition -- Regulation of extracellular fluid composition & volume -- Acidification of the urine & bicarbonate excretion
A Lange medical book;Previous ed.: London: McGraw-Hill Medical, 2010
Includes bibliographical references and index
Authors, Kim E. Barrett, Susan M. Barman, Scott Boitano, Heddwen L. Brooks
Keywords: 2 -- 0; 6; Physiology;Physiology;Physiology -- 20 -- Problems, exercises, etc; 20; Problems, exercises, etc